Sposoby komunikacji swoich potrzeb matkom przez dzieci z zaburzeniami komunikacji językowej - Rybka, Magdalena (Annales Universitatis Paedagogicae Cracoviensis Studia Paedagogica, 2021)
The article present a research report, which aim was examining ways of comunicating children with language development disorders in different age groups. The research shows a series of methods and strategies adopted by the examined childrens. The addition, the author raises the issue of language communication, the nescary conditions and the etiology of disorders